A genome-wide assessment of the ancestral neural crest gene regulatory network - Hockman, Dorit (Nat Commun, 2019)
The neural crest (NC) is an embryonic cell population that contributes to key vertebrate-specific features including the craniofacial skeleton and peripheral nervous system. Here we examine the transcriptional and epigenomic profiles of NC cells in the sea lamprey, in order to gain insight into the ancestral state of the NC gene regulatory network (GRN). Transcriptome analyses identify clusters of co-regulated genes during NC specification and migration that show high conservation across vertebrates but also identify transcription factors (TFs) and cell-adhesion molecules not previously implicated in NC migration. ATAC-seq analysis uncovers an ensemble of cis-regulatory elements, including enhancers of Tfap2B, SoxE1 and Hox-α2 validated in the embryo. Cross-species deployment of lamprey elements identifies the deep conservation of lamprey SoxE1 enhancer activity, mediating homologous expression in jawed vertebrates. Our data provide insight into the core GRN elements conserved to the base of the vertebrates and expose others that are unique to lampreys.